#TITLE_ALTERNATIVE# - Prijambodro (NIM 250 92 023), Bambang
Abstract: Coyle and Reese (1966) proposed a theory concerning the load transfer curve which was further developed by Kraft et al (1981) known as t-z curve. Method of load transfer analysis developed by Reese et al (1966) in fact gave the most rational result as far as the used t-z curve reflecting actual condition. In developing this t-z curve, direct shear test represent an ideal simulation and closely reflected the actual condition for shear interaction modeling between pile and soil. In this research, the t-z curve was developed in sandy soil from direct shear test result in laboratory with application to bored pile. Shear was conducted between concrete surface simulating pile materials with the soil recovered near the location of the pile. At site where samples were retrieved, axial loading test has been conducted on instrumented bored pile. The soil sample was lightly cemented sand. Sample was taken at 16,75 m and 22,75 m depth near the bored pile. It has brittle characteristic and high shear strength with internal friction angle of 48degree and 52degree. The laboratory test result was quite statisfactory indicating the t-z curve from laboratory test has the same characteristic with field t-z curve. Although, there was a slight difference due to the influence of boundary effect in the direct shear test, however the infuence on the cemented sand less significant, because in the field condition the shear stress more concentrated on soil-pile interface. Evaluating on the lateral pressure coefficient was also conducted provide a value of K = 1.1, which was relatively higher compared to conventional assumption. This condition showed that the stress in the pile material-soil interface was quite high.